PENEGAKAN HUKUM TERHADAP PELAKU PUNGLI IURAN SAMPAH DI WILAYAH HUKUM KEPOLISIAN SEKTOR TAMPAN - IRFAN SUTIKNO RAMADHAN; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Illegal levies are one of the crimes committed by every legal subject, bothpeople and legal entities, directly or indirectly. Illegal levies are disgraceful actscommitted to benefit oneself by abuse of power. Illegal levies are a form of crimethat is very familiar to the public. Illegal levies are an act of violation of the lawregulated in the Criminal Code (KUHP) Article 368 of the Criminal Code andArticle 423 of the Criminal Code..The objectives in writing this thesis are: First, to find out law enforcementagainst perpetrators of garbage collection in the jurisdiction of the Handsome SectorPolice . Second, to find out the obstacles faced by law enforcers, especially theHandsome Sector Police against perpetrators of garbage collection. Third, to findout the efforts to overcome the obstacles faced by law enforcers, especially theHandsome Sector Police against perpetrators of garbage dues extortion. The type oflegal research used by the author is a sociological legal research. Thissociological research is a type of research in terms of legal objectives.From the results of the study it was found that law enforcement againstillegal levies was carried out by certain persons outside the Pekanbaru DLHKofficers, namely arrests for 1 x 24 hours and coaching for the perpetrators of theillegal levies. the obstacle faced by law enforcers is that the perpetrators of thecrime of extortion do not fulfill the elements in the crime of extortion, namely inthe absence of elements of violence or threats of violence. The efforts of the Polsekto keep law enforcement in place, namely in the form of providing direction oroutreach to the perpetrators and making a statement that they will not repeat thecrime of extortion again. Author's Suggestion, First, Cooperation between thecommunity and the police is further enhanced so that the police can uncover casesof illegal collection of garbage fees that often occur in the jurisdiction of theTampan Police. Second, it is expected that the police apparatus will make strictersupervision, especially against perpetrators of criminal acts of illegal collectionof waste fees. Third, it is hoped that the Handsome Police will add personnel sothat they can maximize the strength of the assignment of members in the context ofserving the community in order to create public order..Keywords: Law Enforcement-Illegal Fees-Police Sector Pekanbaru